Arbejdsmarkedet - hvad sker der? Bidrag af Margit Groth, Flemming Ibsen, Henning Jørgensen, Reinhard Lund, Olaf Rieper, Anders Rosdahl, Helge Tetzschner og Ann Westenholz. København: Fremad 1981, 214 s., 128 kr. - Mortensen, Nils (Politica, 1981)
-